THE RELATIONSHIP BETWEEN BEHAVIOR AND WORK ACCIDENTS AMONG SHIP CREW (ABK) ON PASSENGER SHIPS - Ifka W Kobis; Melany Kumayas; Fransiskus X Dotulong (PT. Jurnal Center Indonesia Publisher, 2025)
Work accidents are unexpected and undesirable events, and work accidents are related to the employment relationship with the company, hospitals, or community health centers. The employment relationship here indicates that accidents occur as a result of work or while performing work. Occupational health and safety (K3) on ships has long been a concern among the government and businesses. K3 factors are closely related to the performance of ship crew (ABK) and, in turn, to the performance of the company. The more safety facilities available, the less likely work accidents are to occur. This study aims to determine how the Relationship Between Health and Safety Behavior (K3) and Work Accidents Among Ship Crew (ABK) on Passenger Ships. The type of research uses a quantitative method with a Cross Sectional approach. The sampling technique in this study is Total Sampling with a sample size of 31 respondents. Data collection was obtained from direct observation, interviews, and questionnaires. Data analysis was conducted through univariate and bivariate tests, with the hypothesis testing using the Chi-square test at a confidence level (α=0.05). The results showed that there is a relationship between behavior and work accidents, with a value of (p=0.03), indicating a relationship between behavior and work accidents.